Caledonia stern and wild : Scottish identity in Wanganui and Rangitikei 1880-1918 : presented in partial fulfilment of the requirements of a Master of Arts degree in History at Massey University - Annabell, Jessie M (Massey University, 1995)
This thesis is a tentative examination of forms of Scottish national identity in New Zealand within two institutions - the Caledonian Society and the Presbyterian Church. The reason why a small, ephemeral, secular organization is considered on the same basis as a very substantial religious institution such as the Presbyterian Church is that they both derived their character from Scotland. The time - between about 1880 and 1918 - covers a period in which conceptions of national identity were changing, both for Scots in New Zealand and for New Zealanders in general. The area - Wanganui and Rangitikei - is not considered especially Scottish when compared with Otago or Southland. When figures for Otago and Southland are removed from population calculations, however, Wanganui and Rangitikei assume a fresh significance. Proportions of Presbyterians, and proportions of Scottish-born are significantly above the average. [From Introduction.]
Keywords: Scots; Rangitikei District; Wanganui; 19th century; 20th century; History; Immigrants; New Zealand